Pembuatan Paket Informasi Budaya Alam Minangkabau - Lyana, Vira; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract The writing of this paper discusses making the Minangkabau Natural Culture information package. The purpose is to describe the making of an information package for Minangkabau Natural Culture. The method used is descriptive method that is describing what it is or collecting data directly from the original source. After data analized, the conclusion is: 1) setting the topic and type of packaging; 2) collection of information; 3) analysis of the results of the collection of information; 4) packaging information; and 5) evaluation.Keywords: information package; Minangkabau Natural Culture